2007
DOI: 10.1002/anie.200700999
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐to‐Photo‐Switching of the Chromic Behavior of Salicylideneanilines by Inclusion in a Porous Coordination Network

Abstract: Insert and twist: By inclusion in the channel of a porous coordination network, an otherwise thermochromic salicylideneaniline derivative becomes photochromic because its intrinsic planar conformation is transformed into a nonplanar one. The photochromic properties of the nonplanar guest molecule can be tuned by changing the co‐included solvent in the channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 48 publications
0
50
0
1
Order By: Relevance
“…[55,56] Interestingly, N-salicylidene aniline derivatives are only thermochromic in solution because of the low stability of the trans-keto form in this medium. Solid-state optical properties of N-salicylidene aniline derivatives are also influenced by the molecular environment, as shown by the incorporation of these molecules in polymethyl methacrylate, [48] MCM41 mesoporous silica, [57][58][59] liquid crystals, [60] organogelators and clathrates, [61][62][63][64][65][66][67] Na-Y zeolite [59,68] or micelles. [59] More recently, we have shown that the crystal structure was not the only factor to take into account to predict thermo-and photochromism of Nsalicylidene anilines in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…[55,56] Interestingly, N-salicylidene aniline derivatives are only thermochromic in solution because of the low stability of the trans-keto form in this medium. Solid-state optical properties of N-salicylidene aniline derivatives are also influenced by the molecular environment, as shown by the incorporation of these molecules in polymethyl methacrylate, [48] MCM41 mesoporous silica, [57][58][59] liquid crystals, [60] organogelators and clathrates, [61][62][63][64][65][66][67] Na-Y zeolite [59,68] or micelles. [59] More recently, we have shown that the crystal structure was not the only factor to take into account to predict thermo-and photochromism of Nsalicylidene anilines in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in non-crystalline media, planarity is lost and photochromism is systematically observed. These media, such as polymethyl methacrylate films, [16] MCM41 mesoporous silica, [33] liquid crystals, [34] organogelators and clathrates, [24,[35][36][37][38][39] maintain a random orientation of the molecules thus allowing cis/trans isomerisa-Abstract in French: Les relations entre structures cristallines et propriØtØs optiques des N-salicylidne anilines ont ØtØ rØvi-sØes et discutØes à la lumire de nouveaux rØsultats expØrimentaux ainsi que dune approche thØorique. La N-salicylidne 3-aminopyridine (L 3 ) est une molecule thermo-et photochrome qui prØsente une relaxation thermique extrÞmement lente (k = 9,9 10 À8 s À1 ) aprs photo-illumination, ce qui est adaptØ pour des applications telles que les mØmoires optiques.…”
Section: Introductionunclassified
“…[8] This provides an anchor for postsynthetic modification (PSM) reactions that occur in the solid state and can be monitored crystallographically. [9][10][11][12][13][14][15] In the absence of an aromatic handle,m atching of the spatial dimension of the pore cavity is also av iable strategy to observe guests using crystallographic methods.This approach has been used to probe photoswitching, [16] change conformational isomerization ratios, [17,18] observe unusual molecular interactions, [19] and identify organic species, [20,21] with the notable advantage of requiring only nanogram to microgram quantities of the analyte.[3]Arange of chemical reactions have been observed within CMFs,i ncluding the conversion of amines into imines, [9,10] Huisgen cycloadditions, [11] Diels-Alder reactions, [14] and metal-catalyzed methylation [12] and bromination.[15] All of these processes occurred upon immersing aC MF that contained am odified intercalated triphenylene moiety into solutions with appropriate chemical reactants.O nly one example of achemical reaction combining gas-phase reagents and aCMF has been reported, and involved the conversion of avinyl group into epoxidation/oxidation products with the aid of ar adical initiator. [14] This reaction, however,r equired loading of the CMF with 2,2'-azobis(isobutyronitrile) and the use of forcing conditions,whereby an emulsion of crystals was heated at 80 8 8Cf or 24 hours in air.T ot he best of our knowledge,a ttempting chemical transformations in CMFs using gas-phase reagents in the absence of solvents is unprecedented.…”
mentioning
confidence: 99%